2015
DOI: 10.1186/s12985-015-0238-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus in patients with terminal renal disease undergoing dialysis in southern Brazil: prevalence, risk factors, genotypes, and viral load dynamics in hemodialysis patients

Abstract: Hepatitis C (HCV) is a serious public health issue, and it is estimated that 3% of the world’s population is infected. Patients in hemodialysis units have an increased risk for contracting HCV, and high prevalence rates have been found in hemodialysis units around the world. This study is aimed at determining the prevalence of HCV in patients with terminal chronic renal disease (tCRD) who have been submitted to hemodialysis and peritoneal dialysis in southern Brazil to characterize the most prevalent genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
3
19
1
1
Order By: Relevance
“…We evaluated the HCV infection risk factors such as intra venous drug injection, history of blood transfusion, kidney transplantation, duration of dialysis, and tattoo. Our study showed significant relation between positive HCV markers with hemodialysis duration (p<0.001) similar to Somi et (7,20). The high prevalence of HCV among dialysis patients can be related to several risk factors including the number of blood transfusions, dialysis duration and type of dialysis (lower HCV prevalence among peritoneal dialysis patients).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We evaluated the HCV infection risk factors such as intra venous drug injection, history of blood transfusion, kidney transplantation, duration of dialysis, and tattoo. Our study showed significant relation between positive HCV markers with hemodialysis duration (p<0.001) similar to Somi et (7,20). The high prevalence of HCV among dialysis patients can be related to several risk factors including the number of blood transfusions, dialysis duration and type of dialysis (lower HCV prevalence among peritoneal dialysis patients).…”
Section: Discussionsupporting
confidence: 75%
“…Anti HCV in hemodialysis patients is reported 11.6% in the United States to 91% in some developing countries (4,5). The worldwide prevalence of HCV infection in hemodialysis patients approved with reverse transcriptase polymerase chain reaction (RT-PCR) is 5-24% (6,7). Risk factors are known for HCV in hemodialysis patients, including intravenous drug injection, past blood transfusion, kidney transplantation, long duration of dialysis, and tattoo (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the major advances in techniques for the detection and prevention of hepatitis C, the number of patients undergoing dialysis treatments who are infected by this virus in Brazil has increased in recent years (4) . There are estimates indicating that 34,366 individuals begin hemodialysis treatment in Brazil annually, including 5,963 new cases per year in the South.…”
Section: Methodsmentioning
confidence: 99%
“…This is 5 times the rate of infection with human immunodefi ciency virus (HIV) (3) . In Brazil, it is estimated between 2.5% and 4.9% of the population is infected with hepatitis C virus (4) .…”
Section: Introductionmentioning
confidence: 99%